Predictors of Health-Related Quality of Life in Adult Hemophilia Patients in Cipto Mangunkusumo Hospital - Findy Prasetyawaty; Lugyanti Sukrisman; Bambang Setyohadi; Siti Setiati; Marcel Prasetyo (Jurnal Penyakit Dalam Indonesia)
Introduction. Currently, one of the main focus of hemophilia treatment is to increase health-related quality of life. Due to financial constraints, factor VIII substitution is used only on demand in Indonesia, which might contribute to musculoskeletal complications and affect the quality of life of adult hemophilia patients. This study aimed to evaluate quality of life of adult hemophilic patients and its related factors.